How procurement become sustainable for Agro-Meteorological Information Systems Development Project (AMISDP), Department of Agricultural Extension (DAE) under Ministry of Agriculture - Khan, Md. Sanowarul Islam (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.